ECOLOGICAL AND ECONOMIC RESULTS OF SPRUCE DECLINE IN THE UKRAINIAN CARPATHIANS - Shparyk, Y. S. (Forestry and Forest Melioration, 2017)
Introduction The health of Norway spruce (Picea abies (L.) Karst.) sharply declines in the Ukrainian Carpathians for the last decade in most districts and forest types, and the area of dead spruce stands ranges by various estimations between 20 and 50 thousand hectares. Forestry results of the spruce forests decline in the region will be large-scale changing of main forest species from Norway spruce on common beech. The current (an increase of the profit from the increase of volumes of spruce wood logging; reduction of the profit from the loss of spruce wood volumes through decreasing of the volume increment and tree numbers) and long-term (reduction of the profit from the loss of wood prices as a result of change of species composition from spruce on beech; reduction of the profit from the loss of volumes of the logging wood as a result of decreasing of the volume increment and from increasing of the stand maturity age) ecological and economic results of the regional spruce forests decline are analysed in this publication. Materials and Methods The calculation of ecological and economic results of the regional spruce forests decline is realized on research results in the main forest types of the Ukrainian Carpathians: wet pure Norway spruce fairly fertile forest type; wet Common beech - Silver fir - Norway spruce fairly fertile forest type; wet Common beech - Norway spruce - Silver fir fairly fertile forest type. Research methods were traditional for Ukrainian forestry and were applied on 19 permanent research objects with different age of forest and with different stages of spruce decline. Wood prices are taken from the regional commodity exchange. Results The percent of spruce dead wood in the stands was calculated according to spruce decline dynamics on research objects depending on the forest type. The additional volume of the logging spruce wood was approximately 750 thousand m3 per year in the conditions of the wet pure Norway spruce fairly fertile forest type. In the conditions of the wet Common beech - Silver fir - Norway spruce fairly fertile forest type this volume was close to 650, and in the conditions of the wet Common beech - Norway spruce - Silver fir fairly fertile forest type – 290 thousand m3 per year. So, the most profit of the forestry enterprises is possible in the wet pure Norway spruce fairly fertile forest type – close to 627 million UAH per year on all territory of the forest type. Actual losses of a spruce wood as result of spruce decline were calculated according to its volume increment decreasing per tree and according to its tree number decreasing per hectare. Norway spruce volume increment decreasing was estimated on comparison results of spruce growth for diameter on research objects with forest growth table data. And its tree number decreasing was estimated on the number of dead spruce trees. In the wet pure Norway spruce fairly fertile forest type these losses of wood were as follows: 110 thousand m3 per year from volume increment decreasing, and 695 thousand m3 per year from tree number decreasing. Total losses were 258.08 million UAH per year or 3.1 thousand UAH per year on 1 hectare. The long-term results of spruce decline were calculated on a period of 100 years, which contain a beech forest rotation period (100 years) and a spruce forest rotation period (80 years) in these conditions. Long-term losses from spruce volume increment decreasing will be 69.54 m3 or 45.88 thousand UAH per ha for 100 years. Reduction of the profit from the change of the main forest species (from Norway spruce on Common beech) will be only 5.63 thousand UAH per ha. Conclusions The ecological and economic results of spruce decline are different for main forest types of the Ukrainian Carpathians. Average profit from additional volume of logging spruce deadwood is 5.35 thousand UAH per hectare per year. Lack of sanitary cuttings reduces this profit by 30–40 percent. Total actual losses are 12 thousand UAH per hectare per year. The long-term results of the spruce decline in the main forest types are as losses too but their size is small. Therefore, total average losses caused by spruce decline may be close to 7 thousand UAH per hectare per year. Ecological effects will be main species changing on 200–300 thousand hectares of regional forests. 1 Fig., 10 Tables, 15 Refs.